Ritme, Rima, dan Nilai-nilai Pendidikan dalam Kasidah al-'Ilm wa al-Ta'līm wa Wājibul-Mu'allim Karya Ahmad Syauqi - Nurjaman, Fadil; Supriadi, Dedi; Nurlinah, Nurlinah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to explore the changes in rhythm and rhyme, as well as educational values, in Ahmad Shawqi’s kasidah al-’ilmu wa at-ta‘līm wa wājibu al-mu‘allim using a qualitative approach and descriptive-analytical methods. Data collection employed a literature review focused on the primary source, namely al-’ilmu wa at-ta‘līm wa wājibu al-mu‘allim by Aḥmad Šauqī in his Aš-Šauqiyyāt, while data analysis techniques included inventory, classification, and interpretation. In terms of rhythm, this kasidah uses the bahr kamil with ‘aruḍ ṣahīhah, maqṭu‘ muḍmar, and muḍmar. Meanwhile, the ḍarb is maqṭu‘‘ and maqṭu‘ muḍmar. As for the hasywu, some are ṣahīh and others are muḍmar. In terms of rhyme, this kasidah lamiyyah produces an analysis of hudud al-qafiyah, huruf al-qafiyah, harakat al-qafiyah, anwa‘ al-qafiyah, and asma’ al-qafiyah, with no ‘uyub al-qafiyah found, making it beautiful and highly musical. The educational values in this kasidah include respect for teachers, tawhid, ibadah, the use of educational resources, the cultivation of the soul and character, scientific integrity, the chain of generations of educators, education based on justice, the heavy burden of teachers, the role of women in education, tawakal, and ikhtiar. This study indicates that prosody is not just for entertainment; it also includes rhythm and rhyme that convey musicality and can serve as a medium for communicating educational values.